2014
DOI: 10.1179/1362171814y.0000000209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dilution and baseplate strength on stress distributions in multipass welds deposited using low transformation temperature filler alloys

Abstract: Transformation plasticity can be utilised to control residual stresses in steel welds. This requires special filler alloys that transform at a sufficiently low temperature to compensate for accumulated thermal contraction strains. However, the welding parameters needed to optimise the effect in multipass joints have yet to be established. This topic has been investigated by characterising the residual stress distribution in multipass welds fabricated with different welding alloys and baseplates using neutron d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…Dilution is commonly defined as the ratio of the cross-sectional area of melted base material to the total area of the fusion zone [8], hence representing the contribution of base material to the weld metal. Therefore, for a given combination of filler and base materials, the extent of chemical heterogeneity within a weld is influenced by dilution, which can have significant effects on the metallurgical and mechanical behaviour of steel weldments [9][10][11][12]. Despite the important role that dilution plays in welding, dilution has not been considered in most published research on multipass weld modelling [13][14][15].…”
Section: Accepted Manuscript N O T C O P Y E D I T E Dmentioning
confidence: 99%
“…Dilution is commonly defined as the ratio of the cross-sectional area of melted base material to the total area of the fusion zone [8], hence representing the contribution of base material to the weld metal. Therefore, for a given combination of filler and base materials, the extent of chemical heterogeneity within a weld is influenced by dilution, which can have significant effects on the metallurgical and mechanical behaviour of steel weldments [9][10][11][12]. Despite the important role that dilution plays in welding, dilution has not been considered in most published research on multipass weld modelling [13][14][15].…”
Section: Accepted Manuscript N O T C O P Y E D I T E Dmentioning
confidence: 99%
“…Special heats of phases Ci and phase transformation heat are calculated in Equations (11)(12) as functions of phase enthalpy, Hi [29]:…”
Section: Conductivitymentioning
confidence: 99%
“…The effect of dilution and strength of the base metal on the residual stresses distribution in multi-pass welding using LTT fillers has been studied by Ramjavn et al [11]. They concluded that excessive lowering of Ms is not effective in reducing the tensile residual stress and creation of compressive residual stress, in addition, the residual stresses rise again for too low Ms. Also, for a greater degree of dilution and greater amounts of base metal in the fusion zone (FZ), the effect of LTT filler becomes less.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, after adopting the LTT welding consumables, tensile stresses were reduced to zero, and even compressive residual stresses were generated once the transformation temperatures got lower enough [5]. In addition, the dilution has a great influence on the efficiency of LTT welding consumables [8].…”
Section: Introductionmentioning
confidence: 99%